Natural selection and recombination at host-interacting lipoprotein loci drive genome diversification of Lyme disease and related bacteria - Akther, Saymon; Mongodin, Emmanuel F; Morgan, Richard D; Di, Lia; Yang, Xiaohua; Golovchenko, Maryna; Rudenko, Natalie; Margos, Gabriele; Hepner, Sabrina; Fingerle, Volker; Kawabata, Hiroki; Norte, Ana Cláudia; et al. (mBio, 2024)
UNLABELLED: Lyme disease, caused by spirochetes in the Borrelia burgdorferi sensu lato clade within the Borrelia genus, is transmitted by Ixodes ticks and is currently the most prevalent and rapidly expanding tick-borne disease in Europe and North America. We report complete genome sequences of 47 isolates that encompass all established species in this clade while highlighting the diversity of the widespread human pathogenic species B. burgdorferi. A similar set of plasmids has been maintained throughout Borrelia divergence, indicating that they are a key adaptive feature of this genus. Phylogenetic reconstruction of all sequenced Borrelia genomes revealed the original divergence of Eurasian and North American lineages and subsequent dispersals that introduced B. garinii, B. bavariensis, B. lusitaniae, B. valaisiana, and B. afzelii from East Asia to Europe and B. burgdorferi and B. finlandensis from North America to Europe. Molecular phylogenies of the universally present core replicons (chromosome and cp26 and lp54 plasmids) are highly consistent, revealing a strong clonal structure. Nonetheless, numerous inconsistencies between the genome and gene phylogenies indicate species dispersal, genetic exchanges, and rapid sequence evolution at plasmid-borne loci, including key host-interacting lipoprotein genes. While localized recombination occurs uniformly on the main chromosome at a rate comparable to mutation, lipoprotein-encoding loci are recombination hotspots on the plasmids, suggesting adaptive maintenance of recombinant alleles at loci directly interacting with the host. We conclude that within- and between-species recombination facilitates adaptive sequence evolution of host-interacting lipoprotein loci and contributes to human virulence despite a genome-wide clonal structure of its natural populations. IMPORTANCE: Lyme disease (also called Lyme borreliosis in Europe), a condition caused by spirochete bacteria of the genus Borrelia, transmitted by hard-bodied Ixodes ticks, is currently the most prevalent and rapidly expanding tick-borne disease in the United States and Europe. Borrelia interspecies and intraspecies genome comparisons of Lyme disease-related bacteria are essential to reconstruct their evolutionary origins, track epidemiological spread, identify molecular mechanisms of human pathogenicity, and design molecular and ecological approaches to disease prevention, diagnosis, and treatment. These Lyme disease-associated bacteria harbor complex genomes that encode many genes that do not have homologs in other organisms and are distributed across multiple linear and circular plasmids. The functional significance of most of the plasmid-borne genes and the multipartite genome organization itself remains unknown. Here we sequenced, assembled, and analyzed whole genomes of 47 Borrelia isolates from around the world, including multiple isolates of the human pathogenic species. Our analysis elucidates the evolutionary origins, historical migration, and sources of genomic variability of these clinically important pathogens. We have developed web-based software tools (BorreliaBase.org) to facilitate dissemination and continued comparative analysis of Borrelia genomes to identify determinants of human pathogenicity.
Keywords: sekvenování celého genomu; Lipoproteins; Borrelia burgdorferi komplex; Plasmids; lymeská nemoc; Borrelia burgdorferi; klíště; genetická variace; fylogeneze; lipoproteiny; Lyme Disease; Phylogeny; genome diversification; recombination; Genome, Bacterial; Europe; molekulární evoluce; Evolution, Molecular; Borrelia burgdorferi Group; plasmids; Selection, Genetic; Evropa; interakce mikroorganismu a hostitele; selekce (genetika); genom bakteriální; Host Microbial Interactions; Animals; lidé; Humans; evolution; zvířata; Recombination, Genetic; rekombinace genetická; plazmidy; North America; Ixodes; Borrelia; Genetic Variation; Lyme disease; Whole Genome Sequencing; Severní Amerika